BENTUK PENYAJIAN DAN PROSES PENCIPTAAN TARI NELAYAN KARYA MARTOZET - Dastri Sinan Wilis Harahap (Universitas Negeri Medan, 2016)
Tor -tor dance IlahMardidong is growing and developing in Simalungun . Tor- tor dance is atradition that has been rearranged forms of the movement in 1985 by a man named Lina BrDamanik . The purpose of this study is to discuss the tor-tor IlahMardidong viewed from thestandpoint of choreographic form.The theory used in this research is the theory of Forms choreography Sudarsono which containsabout : motion , theme , design floors , top design, fashion and music . This theory became areference for peeling the existing problems in the tor- tor god mardidong .When the study to discuss IlahMardidong dance performed during 3 months ,ie from the beginningof October 2015 through December 2015. The study in the village of Huta III Glare Malela . GlareSubdistrictMalela . The population is three persons namely speakers , traditional leaders , andartists who know about the culture Simalungun . samples in this study were of three personsnamely speakers , traditional leaders and artists in Simalungun . Data collection techniquesincluding observation , interviews , literature study and documentation , which is then analyzed byqualitative descriptive method .Based on research done that tor-tor IlahMardidong have a soft form of motion,tortorIlahMardidong wear internal musical accompaniment is music that is born out of the humanbody . Clothing used in this Tortor is yeast pane ,surisuri and headdress silappei . The themescontained in this dance is the hope of a mother for her child , and the top design contained in thisdance is the design in the design, low design and asymmetrical design